Human Aging and Pharmacology of Opioids. A Point for Reflexion - Belkys Quintana López (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2012)
Life expectancy has been significantly increased worldwide. This phenomenon has caused changes in disease patterns, with a high prevalence of chronic pain in over 65 years old patients, specifically non-oncological pain. The challenges imposed for their treatment are not avoidable and potential success lays in the knowledge of the peculiarities of the elderly and the drugs used to treat pain. All these can be achieved if professionals know the major physiological changes and pathological conditions associated with aging, as well as the pharmacology of opioids, an interaction that is more important for these purposes than prescription itself, as the changes caused by aging and the diseases present in each patient in particular may affect all processes in the intraorganic cycle of drugs. All of these factors should be taken into consideration at the beginning and during the treatment. This work approaches to recommendations for the therapeutic approach of opioids, not getting deep in the individuality of each product considering that there is no evidence of the use of all them the elderly. Therefore, only those for which there is evidence are addressed.